Case studies of creating reusable inter professional e-learning objects - Wharrad, Heather; Windle, Richard (IGI Global, 2010)
Reusable learning objects can play an important part in enhancing interprofessional learning. They provide flexible support to students of health care and provide an opportunity during the creation process, for interprofessional educators to share knowledge and understand more about each other’s roles. When creating learning objects, a development and evaluation framework including technical expertise and quality control at critical stages is important, however it is the interprofessional community brought together at workshops at the start of the development cycle and the underlying pedagogical design principles that ensure the materials are fit for purpose and guarantee reuse across professional groups.